2011
DOI: 10.5171/2011.670212
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of ERP System Implementation on Business Performance: An Exploratory Case-Study

Abstract: There is currently plenty of research concerning the effect of Enterprise Resource Planning (ERP) Systems on business performance. Previous research has shown a mixed relationship between ERP and business performance where some suggested that ERP improves performance and others found that it does not. Previous research was mainly based on quantitative methods which don't give important insightful knowledge and details. A case-study on the other hand can help identify the important contributing factors for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 25 publications
1
20
0
1
Order By: Relevance
“…Hence, the customer capital is also affected by the process capital, ultimately translating it into business performance. Elragal andAl-Serafi (2011) andPoston andGrabski (2000)also support the positive contribution of ERP on OP. Elragal and Al-Serafi (2011)found that the positive contribution of ERP mainly comes from increase efficiency in information diffusion which enable organizations to response faster and improve the management of inventory.…”
Section: Enterprise Resource Planning and Organizational Performancementioning
confidence: 71%
See 1 more Smart Citation
“…Hence, the customer capital is also affected by the process capital, ultimately translating it into business performance. Elragal andAl-Serafi (2011) andPoston andGrabski (2000)also support the positive contribution of ERP on OP. Elragal and Al-Serafi (2011)found that the positive contribution of ERP mainly comes from increase efficiency in information diffusion which enable organizations to response faster and improve the management of inventory.…”
Section: Enterprise Resource Planning and Organizational Performancementioning
confidence: 71%
“…Elragal andAl-Serafi (2011) andPoston andGrabski (2000)also support the positive contribution of ERP on OP. Elragal and Al-Serafi (2011)found that the positive contribution of ERP mainly comes from increase efficiency in information diffusion which enable organizations to response faster and improve the management of inventory. Poston and Grabski (2000) argue that ERP contributes to cost reduction and thus revenue enhancement.…”
Section: Enterprise Resource Planning and Organizational Performancementioning
confidence: 71%
“…In [10] Elragal et. al represented a case study that showed relationship between ERP and business performance.…”
Section: Related Workmentioning
confidence: 99%
“…ERP systems reduce costs, exchange information in a better way, and reduce response time between customers and suppliers [9]. An ERP system can be operated within the enterprise with one standard application that provides integration between all supporting departments such as sales, accounting, manufacturing, human resources and supply chain [10].…”
Section: Introductionmentioning
confidence: 99%
“…Sayed et al, 2013). For instance, some scholars investigate factors affect the success of ERP (Abdelghaffar and Azim, 2010) and others identified factors contribute towards the relationship between business performance and ERP (Elragal and Al-Serafi, 2011) and the influence of cultural challenge on ERP adoption in Egypt, which differs from the other cultures from where the system of ERP is originated (El Sawah et al, 2008). However, recent surveys showed that the success rate of ERP implementations in Egypt is extremely lower than it is in western enterprises, and half of the ERP implementations in Egypt are considered as failures (Abdellatif, 2014).…”
Section: Introductionmentioning
confidence: 99%